Comparison of standard image edge detection techniques and of method based on wavelet transform - Kobylin, O.; Lyashenko, V. (IJAR, 2014)
Image edge detection is in the forefront of image processing. There are lots of various edge detection methods. However the choice of a certain image edge detection technique still remains topical and this issue is constantly in focus for the researchers. This owes to both the specifics of implementing certain image edge detection technique and to the specifics of obtaining and presenting images for further processing. Based on this, in this paper, the comparison of standard image edge detection techniques (Canny, Prewitt, Robert, Sobel) and methods based on wavelet transform are studied. Quantitative measures for evaluating edge detection quality and simple visual comparison of the obtained edge maps of the original image are used for comparison. The advantages and disadvantages of these edge detection techniques have been shown.
Keywords: image; wavelet transform